The archaeology of the Ifugao agricultural terraces antiquity and social organization - Acabado, Stephen (ProQuest Dissertations & Theses Global, 2010)
"This project explores the relationship between irrigation management and social organization of the Ifugao in the Northern Philippines. Agricultural intensification studies in traditional societies shed light on the relationship between increasing social stratification and production intensification. While archaeologists have long associated large-scale agricultural systems with centralized political organization, recent anthropological studies have identified the limitations of this assumption. This historical ecological study examines the sustainability of Ifugao irrigated-terrace farming, and documents dynamic and recursive linkages between the Ifugao and their environment. Its focus on the apparent disjunction between water management and sociopolitical stratification identifies factors that underlie the sustainability of Ifugao agriculture, and structural correlates that generate an intensive agricultural landscape. The sustainability of Ifugao agriculture is related to the social structure that links individuals through attachment to the agricultural field. As such, this investigation establishes the nature of Ifugao social organization through the "house" concept. Corollary to determining cultural patterns in Ifugao, this project aims to resolve debates on the antiquity of the entire Cordillera terraced field tradition. Archaeological and ethnohistoric work will confirm whether the conventional 'long history' or the revisionist 'short history' more accurately represents the occupational history of this region. The research uses multiple methods to investigate the history and growth of the highland Ifugao system: (1) Geographic Information Systems technology to identify the topographic locations that were best suited for settlement and terrace construction; (2) archaeological excavations to determine the age of individual settlements and terraces, and (3) ethnographic research with Ifugao farmers to determine how labor is deployed to construct and maintain their irrigation terraces. Research sites are located in the UNESCO World Heritage Sites of Ifugao Province (Cordillera, Philippines), where little previous archaeological research has been undertaken. The need for such research is particularly urgent because the area's ancient terraces are rapidly deteriorating as increasing numbers of Ifugao farmers leave their traditional farming occupations and their rice terraces fall into disuse. This study will generate archaeological findings that are directly relevant to understanding and preserving Ifugao irrigation technology and heritage, and also expands our anthropological knowledge of water management in the non-industrial world."--Abstract.